Production, nutritional benefits, limitations and strategies for enhancing the national value of fermented native condiments from selected legumes and wild seeds in Nigeria - Oluwatoyin Ajoke Oladeji; Kehinde Adekunbi Taiwo; Clement Olusola Ogidi; Adeyanmola Oluwaseyi Faturoti (Discover Food)
Abstract Condiments are additives used in small quantities to enhance food flavour before, during, or after cooking. Research has shown that native Nigerian condiments (such as Iru, Ogiri, Owoh, Okpei, and Ugba), offer significant nutritional benefits and could serve as functional foods. However, the consumption of these native condiments is limited by various factors including poor processing conditions, unacceptable packaging and ineffective marketing strategies. This review, based on various studies, research articles, books, book chapters and Google sites, focuses on the production of traditional African condiments, particularly in Nigeria. It discusses their health benefits, nutritional quality, and potential to address malnutrition. The review also reports on recent improvements in production, packaging, and marketing strategies, and suggests good manufacturing practices to enhance quality, consumer acceptability, industrialization, and national value. The study indicated that with appropriate improvements in production processes, packaging and marketing strategies, native condiments have considerable potential to contribute to nutrition, health, economic growth, and improve food security in Nigeria and other African countries.